Structure of of Bis(O,O’-dialkyldithio-phosphato) Dimeric Silver(I) with Bis(1,10-phenanthroline): Ag2[(PhO)2PS2]4(Phen)2 and Ag2[(PrO)2PS2]4(Phen)2 - JIAN, FANGFANG; XIAO, HAILIAN; SUN, PINGPING (Asian Journal of Chemistry, 2010)
The crystal and molecular structures of Ag2[(PhO)2PS2]4(Phen)2 and Ag2[(PrO)2PS2]4(Phen)2 (Phen = 1,10-phenanthroline) have been determined by X-ray crystallography. The crystal structures in two complexes are difference. The former crystallizes in the monoclinic system, space group P2(1)/c, with lattice parameters a = 11.140(2), b = 10.044(2), c = 23.006(6) Å, β = 113.36(3)° and Z = 4. The latter crystallizes in triclinic, P-1, with a = 9.875(2), b = 10.992(2), c = 11.232(2) Å, α = 68.32(3), β = 99.55(3), γ =65.16(3)° and Z = 2. The molecular structures of them are similar. They all display distorted tetrahedral geometry around the central silver atom. The two dialkyldithiophosphato ligands bridge two silver atoms to form an eight-membered Ag2S4P2 ring, while the 1,10-phenanthroline molecule coordinates to a silver atom to complete the local tetrahedral geometry. The Ag···Ag separation in the two dimer are 3.185(2) and 3.207(1) Å, respectively.